Directions of innovative activities in the process of preparation of masters specialties «Geodesia and land management» - Фоменко, Г. Р.; Ряпухін, В. М.; Саркісян, Г. С.; Синовець, О. С. (Scientific notes of the pedagogical department, 2019)
In modern condi ons, masters training should meet the requirements that make it impera ve to improve the quality of the educa on system, and at the same me, its compe veness at the interna onal level. The eﬀec veness of master’s training is aimed at increasing their professionalism and independence in solving modern problems in the chosen specialty. Forma on of the image of a specialist of innova ve type in the field of «Geodesy and land management» is possible in the magistracy of ins tu ons of higher educa on, focused on training, both for research and professional ac vi es. Innova ve educa on is focused on crea ng the condi ons for the individual’s readiness for change, the development of crea ve abili es, various forms of thinking, and coopera on. The specificity of innova ve educa on is determined by its openness, the predic on of results based on the constant assessment of values, the ability to act together in emerging new situa ons. Master training is an important, promising, alterna ve ac vity. A future master should have not only fundamental knowledge, but also be able to create something new on the basis of crea ve thinking. Therefore, it is necessary to organize a single educa onal, scien fic and innova ve space, which includes educa onal, research and produc on components. In modern condi ons, research and innova on ac vi es are closely linked. On the one hand, innova on ac vi es at the early stages include research and development ac vi es, namely, fundamental and applied research and experimental development. On the other hand, one of the func ons of research ac vity is innova on. The main components of the readiness of masters for professional ac vi es, innova ve research work include: mo va onal, conforma onal, opera onal. Mo va on research ac vity is a system of actors that include: mo ves, needs, interests, inclina on, mo va onal a tudes, which make it possible to ensure the realiza on of the purpose of this ac vity. For the mo va onal sphere of the personality, stamina and strength of mo ve are of great importance. Moves of knowledge are able to form a master’s achievement mo va on. Mo ves of knowledge create condions for overcoming crisis situa ons, improve cogni ve ac vity and form the founda on of competence.